Financial Literacy for Bundo Kanduang in Improving the Quality of Household Financial Management : Literasi Keuangan bagi Bundo Kanduang dalam Meningkatkan Kualitas Pengelolaan Keuangan Rumah Tangga - Taqwa, Salma; Sari, Vita Fitria; Delfiani, Silvi; Ridhaningsih, Fitria; Jefri, Riny (Yayasan Ahmar Cendekia Indonesia, 2024)
The results of the 2022 national survey showed that the financial literacy rate in West Sumatra was 40.78%, far below the national average, and ranked in the bottom 3 in Sumatra. Therefore, various efforts are needed to improve financial literacy. This community service activity focuses on financial literacy in household financial management considering the many financial problems in households due to the lack of knowledge of housewives in managing household finances. The object of this activity is the Bundo Kanduang organization in West Air Tawar. In Minangkabau, Bundo Kanduang acts as the guardian of the Rumah Gadang who is responsible for the Rumah Gadang, high heirloom property, and is also a symbol for his people and is expected to be a role model for the society. The proposing team provided training to enhance the financial literacy of Bundo Kanduang through simple bookkeeping and good financial planning in order for upgrading the quality of household financial management. By the time the activity ended, 72.5% of the material and cases had been well understood by the participants. After this activity, it is hoped that mothers can practice the knowledge that has been given and can share their knowledge with housewives in their environment.